Business writing in the digital age - Canavor, Natalie, 1942- (Thousand Oaks, Calif. : SAGE, 2012)
'Business Writing for the Digital Age: A Student's Guide can be used as a core or supplementary text for business writing courses and across the Business and Management curriculum as a student aid to better writing. The text instructs business students how to write for the 21st century business environment in the style it demands: clearly, concisely, powerfully, and with individuality. It also addresses explicitly the digital realm of email, social networking, and social media strategies. The text gives writing teachers a complete structure for teaching business writing that they can adapt to their own preferences. It is also useful for professors who teach general business subjects and recognize a need to help their students write better--a need that is almost universally acknowledged. To serve these dual purposes, the book offers a flexible resource. Its lessons can be taught progressively, drawing on the assignments and discussion questions included. Or, teachers can choose to spend little class time explicitly on writing and instead, assign the book as independent study and evaluate writing progress as a component of regular assigned projects'--
1. Business writing in the digital age-- and you -- 2. Writing strategically --- 3. Putting strategic ideas to work -- 4. Good sentences, the right words: the heart of good writing -- 5. The whole picture: pulling your best message together -- 6. E-mail: your everyday chance to build a professional image -- 7. Letters: they still count -- 8. Writing to persuade part 1: the tools and techniques -- 9. Writing to persuade part 2: creating business documents -- 10. Writing for websites and the wired world -- 11. Business meets the interactive world: blogging, social media and micromedia -- 12. Presenting yourself: rum and elevator speeches.
Includes bibliographical references and index.
Keywords: Business writing; Business communication